CONSUMERS’ WILLINGNESS TO PAY FOR PLASTIC BAGS - Yosini Deliana; Lucyana Trimo; Sri Fatimah; Mohamad Djali (Universitas Padjadjaran, 2023)
The use of plastic bags has become a habit, there is no day without a plastic bag. Seeing the importance of this problem, the government established a regulation for paying plastic bags in supermarkets in 2015, which is Rp. 200,- per sheet, and it is up to May 31, 2016. This policy did not work well and since 2016 supermarkets have returned to using plastic bags without paying for them. The aims of this study were (1) to analyze consumers’ willingness to pay more for plastic bags, (2) to analyze the cluster of consumer knowledge about plastic bags which damage the environment, (3) to analyze the most important factor that consumer will pay more for plastic bags . The study was conducted from May- June 2021 in Bandung, with simple random sampling. The results showed that generally consumers are willing to pay more for plastic bags (willingness to pay) between Rs. 500, - to Rs, 2.000, -, .Consumers who aware that plastic bags destroy the environment was 14.70 %, the medium knowledge was 63.39 % and the low knowledge was 21.91 %. Although the respondent’s knowledge is high, waste disposal is often practiced using plastic bags. Thus, it is not directly proportional to respondents’ knowledge and behavior about plastic bags. The most important factors that consumers are willing to pay for plastic bags are gender and family. This study can be considered for Ministry of Environment, Modern Retail, stakeholders and other market agents in considering the use of plastic bags.